The importance of student journalism: analysis of international experience - Uzoqova, Shahnoza Beknazarovna (The Lingua Spectrum, 2026)
This article analyzes the role and significance of student journalism in the journalism education system based on international experience. The study examines the article “Why student journalism matters” published in The Washington Post through qualitative analysis methods. The research reveals the importance of student journalism in developing professional competencies, strengthening editorial independence, improving critical thinking skills, and helping future journalists adapt to the real media environment. In addition, international media practices are comparatively interpreted in relation to journalism education and media activities in Uzbekistan. The findings demonstrate that journalism education should focus not only on theoretical knowledge but also on practical media activities, independent content creation, and stronger cooperation between media organizations and educational institutions. The study emphasizes the necessity of transforming journalism education from a purely informational approach into a practical and analytical model. At the end of the article, scientific and practical conclusions and recommendations for improving journalism education are proposed.